Different Gene Families in Arabidopsis thaliana Transposed in Different Epochs and at Different Frequencies throughout the Rosids([W]) - Woodhouse, Margaret R. (American Society of Plant Biologists, 2011)
Certain types of gene families, such as those encoding most families of transcription factors, maintain their chromosomal syntenic positions throughout angiosperm evolutionary time. Other nonsyntenic gene families are prone to deletion, tandem duplication, and transposition. Here, we describe the chromosomal positional history of all genes in Arabidopsis thaliana throughout the rosid superorder. We introduce a public database where researchers can look up the positional history of their favorite A. thaliana gene or gene family. Finally, we show that specific gene families transposed at specific points in evolutionary time, particularly after whole-genome duplication events in the Brassicales, and suggest that genes in mobile gene families are under different selection pressure than syntenic genes.